Patients With Uncomplicated Coronavirus Disease 2019 (COVID-19) Have Long-Term Persistent Symptoms and Functional Impairment Similar to Patients with Severe COVID-19: A Cautionary Tale During a Global Pandemic. (6th February 2021) - Jacobson, Karen B; Rao, Mallika; Bonilla, Hector; Subramanian, Aruna; Hack, Isabelle; Madrigal, Martina; Singh, Upinder; Jagannathan, Prasanna; Grant, Philip
Abstract: To assess the prevalence of persistent functional impairment after coronavirus disease (COVID-19), we assessed 118 individuals 3–4 months after their initial COVID-19 diagnosis with a symptom survey, work productivity and activity index questionnaire, and 6-minute walk test. We found significant persistent symptoms and functional impairment, even in non-hospitalized patients with COVID-19.